IMPACT OF SMART INFRASTRUCTURE IN ECOTOURISM INDUSTRY (British Journal of Global Ecology and Sustainable Development, 2025)
Building smart infrastructure plays a crucial role in advancing sustainable tourism. To reach goals from the UNWTO 2030 agenda, tourism must work hard to create a sustainable environment. Using AI, big data analysis, and IoT are some parts or methods to build smart infrastructure that can impact tourism. To promote sustainable travel, there is an ecotourism industry. The government also needs to consider building smart infrastructure as soon as possible and look through the long-term benefit.